IP Telephony Server Emulation for Monitoring and Analysis of Malicious Activity in VOIP Network - Safarik, Jakub; Voznak, Miroslav; Rezac, Filip; Macura, Lukas (Communications - Scientific letters of the University of Zilina, 2013)
The paper aims at gathering information about attacks from real internet infrastructure and their analysis. For this purpose, we prepared a set of honeypots monitoring various aspects of VoIP infrastructure including SIP endpoint and SSH terminal emulation. SIP endpoints are registered with real SIP registrar and the incoming calls are routed to a honeypot according the rules in dialplan. The honeypot gathers valuable data about hacker’s activity with no threat to production systems. Analysis of the honeypot data is crucial for further improvement of existing security mechanisms in VoIP networks. The paper describes the honeypot’s behaviour and brings an analysis of a detected malicious activity as well.